Investigation of Hospital Telephones In Regard with Bacterial Contamination - Özden, Mehmet; Kılıçoğlu, Aydan; Akbulut, Hatice Handan; Akbulut, Ayhan; Felek, Süleyman (Fırat University, 2001)
This study was carried out to define the bacteriological contamination of hospital telephones which were used by a lot of people and to determine risks of this contamination for nosocomial infections. Seventy-three samples were obtained by broth wetted swabs from telephones. These samples were inoculated to Eosin Methylene Blue and 5% sheep blood agar. After 48 hours of incubation, colonies were identified. The growth was determined in 63 mouthpieces ( % 86) and 72 handles ( % 99) of these telephones. The most frequently observed bacterium was coagulase negative staphylococcus; in 54 mouthpieces (% 78) and 68 handles (% 93) in telephones. The bacterium grown are as follows: Staphylococcus aureus 4 (% 5), Streptococcus pneumoniae 12 (% 16), Klebsiella pneumoniae 2 (%3), Escherichia coli 2 (%3) in telephone mouthpieces. On the handles of telephones, these bacteria were: S. aureus 4 (% 5), S. pneumoniae 3 (% 4). As a result, telephones were found to be direct contamination by hands and airborne contamination at our hospital. These results suggest that telephones must be cleaned and disinfected. Especially; education of healthcare personnel seems quite important about hand washing.

Bu çalışma sık kullanılan hastane telefonlarının bakteriyolojik kontaminasyonunu belirlemek ve hastane infeksiyonları açısından risklerini saptamak amacıyla yapıldı. Fırat Tıp Merkezi' nin, kişiye özel ve hasta telefonları olmak üzere toplam 73 telefondan buyyonla ıslatılmış eküvyonlarla alınan örnekler % 5 koyun kanlı agara ve Eosin Methylene Blue besiyerine ekildi. 48 saatlik inkübasyonu takiben üreyen bakteriler tanımlandı. 73 telefondan 63'ünün (% 86) mikrofonlarında, 72'sinin (%99) ahizelerinin elle tutulan kısımlarında üreme tesbit edildi. En fazla üreyen bakteri koagülaz negatif stafilokok idi ve 54 telefonun mikrofonlarında (%78), 68 telefonun elle tutulan kısımlarında (%93) saptandı. Mikrofon kısmında; Staphylococcus aureus'un 4 (%5), Streptococcus pneumoniae'nın 12 ( %16), Klebsiella pneumoniae' nın 2 (% 3), Escherichia coli' nin 2 (%3) telefonda ürediği saptandı. Ahizelerin elle tutulan kısmında ise S. aureus'un 4 (%5), S. pneumoniae' nın 3 (%4) telefonda ürediği gözlendi. Sonuç olarak; hastanemizdeki telefonlarda direkt el ile kontaminasyonun ve solunum yolu ile kontaminasyonun olduğu görülmüştür. Telefonların belirli aralıklarla temizlenmesi ve özellikle hastane personelinin el yıkama konusunda eğitilmelerinin önemli olduğu kanaatine varılmıştır.
HASTANE TELEFONLARININ BAKTERİYEL KONTAMİNASYON AÇISINDAN İNCELENMESİ